Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1038/pr.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the metabolic rate of oxygen in preterm infants during indomethacin therapy for closure of the ductus arteriosus

Abstract: Background:The aim of this study was to assess and quantify the effects of indomethacin on cerebral blood flow (CBF), oxygen extraction fraction (OEF), and cerebral metabolic rate of oxygen (CMRO 2 ) in preterm infants undergoing treatment for a patent ductus arteriosus (PDA). Methods: CBF and CMRO 2 were measured before and after the first dose of a 3-d course of indomethacin to close hemodynamically significant PDA in preterm neonates. Indocyaninegreen (ICG) concentration curves were acquired before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
4
17
0
Order By: Relevance
“…Previous studies have shown that infusing indomethacin over relatively short periods (30 min or less) will have measurable effects on cerebral hemodynamic [34,35]. We have previously demonstrated that despite these hemodynamic effects, basal CMRO 2 is maintained, even at this early age, by an increase in cerebral oxygen extraction [27]. The reduction in StO 2 observed in the current study agrees with the concept of a compensatory adjustment in…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have shown that infusing indomethacin over relatively short periods (30 min or less) will have measurable effects on cerebral hemodynamic [34,35]. We have previously demonstrated that despite these hemodynamic effects, basal CMRO 2 is maintained, even at this early age, by an increase in cerebral oxygen extraction [27]. The reduction in StO 2 observed in the current study agrees with the concept of a compensatory adjustment in…”
Section: Discussionsupporting
confidence: 89%
“…The purpose of the current work was twofold: To measure CBF, StO 2 and CMRO 2 in preterm infants diagnosed with patent ductus arteriosus (PDA) who were undergoing treatment with indomethacin. This treatment group was selected because of the well-known vasoconstricting effects of indomethacin, which provides the opportunity to assess if differential spectroscopy can measure the expected decrease in StO 2 required to maintain normal CMRO 2 [27]. CBF was measured before and after indomethacin treatment using ICG as an intravascular contrast agent [23].…”
Section: Introductionmentioning
confidence: 99%
“…This system has previously been used in a neonatal piglet model [13,14] and neonatal patients at our center. [15] The optical fibers were attached to the head either using a fiber holder headband, or using the CPAP cap to support the fiber holder. We obtained broadband spectra from 600-980 nm at approximately 0.3 nm spectral resolution using a holographic grating coupled to a cooled CCD.…”
Section: Cerebral Spectral Measurements From Cw Systemmentioning
confidence: 99%
“…9,10 With this technique, the concentrations of tissue chromophores, both endogenous and exogenous, are quantified by first or second differential analyses, which exploit the hyper-spectral content of the measurements. 14 Critical to broadband CW-NIRS monitoring is efficient light collection since only a small fraction of the injected light emerges from the probed tissue due to absorption and strong scattering. [11][12][13] More recently, it has been adapted to clinical studies to investigate potential pharmacological effects on cerebral hemodynamics and metabolism in preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] More recently, it has been adapted to clinical studies to investigate potential pharmacological effects on cerebral hemodynamics and metabolism in preterm infants. 10,[14][15][16] Nevertheless, off-the-shelf spectrometers have attractive advantages compared to custom-made units, such as low cost, small footprint, and wide availability. The most common method for improving light collection is by optimizing the contact area between the detection system and the probed tissue by means of light guides with large detection surface.…”
Section: Introductionmentioning
confidence: 99%